Automated labeling for unsupervised neural networks: a hierarchical approach - Tagliaferri, R.; Capuano, N.; Gargiulo, G. (IEEE transactions on neural networks, 1999)
In this paper a hybrid system and a hierarchical neural-net approaches are proposed to solve the automatic labeling problem for unsupervised clustering. The first method involves the application of nonneural clustering algorithms directly to the output of a neural net; and the second one is based on a multilayer organization of neural units. Both methods are a substantial improvement with respect to the most important unsupervised neural algorithms existing in the literature. Experimental results are shown to illustrate clustering performance of the systems.